Bennettitalean Leaves From the Permian of Equatorial Pangea—The Early Radiation of an Iconic Mesozoic Gymnosperm Group - Blomenkemper, Patrick; Bäumer, Robert; Backer, Malte; Abu Hamad, Abdalla; Wang, Jun; Kerp, Hans; Bomfleur, Benjamin (Frontiers in Earth Science, 2021)
Bennettitales is an extinct group of gymnosperms that are among the most iconic plants of Earth’s vegetation during the Mesozoic Era. The sudden appearance and rise to dominance of the Bennettitales during the Triassic remains a mystery. Leaf fossils similar to typical bennettitalean foliage occur in late Paleozoic deposits worldwide, but bennettitalean foliage can be identified with certainty only in case the fossils are sufficiently well-preserved to show epidermal features. So far, the characteristic stomatal architecture of the group has never been documented in these putative Paleozoic remains. Here, we present well-preserved bennettitalean leaves from Permian deposits in two widely separated regions of equatorial Pangea. Two species of cuticle-bearing leaf compressions from the late Permian Umm Irna Formation, Jordan, are here formally described as Pterophyllum pottii Bomfleur et Kerp sp. nov. and Nilssoniopteris jogiana Blomenkemper et Abu Hamad sp. nov. Moreover, bulk maceration of samples from the Umm Irna Formation yielded six additional types of dispersed bennettitalean cuticles that are here informally described. In addition, the Wuchiapingian (early late Permian) uppermost part of the Upper Shihhotse Formation exposed at the Palougou section in Shanxi Province, China, has yielded the oldest unambiguous bennettitalean fossils known to date; they consist of fragments of entire-margined leaves with well-preserved cuticles that we assign to Nilssoniopteris shanxiensis Bäumer, Backer et Wang sp. nov. Notably, the cuticles of these Permian bennettitalean remains show peculiar, apparently plesiomorphic epidermal features—such as non-sinuous anticlinal walls, greater variety in stomatal orientation, and rare occurrence of transversely divided subsidiary cells—that have until now only been documented from the hitherto oldest cuticle-bearing bennettitalean material from the Middle and Upper Triassic. Finally, the taxonomic richness, disjunct distribution, and broad variety in macro- and micromorphological features in these Permian bennettitalean remains lead us to suspect that the origin of the group will date back still further in time, and might in fact coincide with very early occurrences of Bennettitales-like foliage from the Pennsylvanian and Cisuralian, such as Pterophyllum cottaeanum, P. eratum, or P. grandeuryi.